Penerapan Model Problem Based Learning terhadap Hasil Belajar Siswa Kelas IV UPTD SD Inpres Perumnas 2 : Implementation of Problem Based Learning Model on Learning Outcomes of Grade IV Students of UPTD SD Inpres Perumnas 2 - Viola A. Koehoea; Silvester P. Taneo; Treesly Y.N Adoe (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The learning process that does not focus on student needs causes low learning outcomes. This is evidenced by the problems in the field, namely the learning outcomes of grade IV students of UPTD SD Inpres Perumnas 2 during the Mid-Semester Summative; only 13 students have completed it out of 30 other students. Thus, this study aims to improve student's learning outcomes by applying the Problem-Based Learning model. This study uses the Classroom Action Research method, with data collection techniques through observation and tests. This study consists of two consecutive cycles, namely cycle I and cycle II. The results of the cycle I showed that 13 students (43.33%) had achieved the criteria for achieving learning objectives or had been declared complete because students always listened to the teacher's explanation and could work on evaluation questions correctly. While the other 17 students (56.67%) had not been declared complete because students were not focused on learning, even students had not done the evaluation questions properly. Student learning outcomes in cycle II showed a significant increase in student learning outcomes, with 26 students (86.67%) achieving KKTP or declared complete because the students were active, listened to the teacher's explanation, and did the evaluation questions well. The other 4 students (13.33%) did not achieve KKTP because they did not give their opinions during the discussion, disturbed each other, and could not even do the evaluation questions correctly. The completion of student learning outcomes in cycle II had reached 86.67%, so it was included in the very good criteria. It is known that learning by implementing the Problem-Based Learning model is very effective and can improve student learning outcomes.